Study of Diesel Combustion Combined with Hydrogen using an Industrial Burner - Sirachat Premsathit; Arkom Palamanit; Mohideen Batcha, Mohd Faizal; Makatar Wae-hayee (International Journal of Integrated Engineering, 2025)
Facing the challenges of fossil fuel depletion and greenhouse gas emissions, there is an urgent need to study and find new energy sources that are both efficient and non-polluting. This research aims to investigate the effects of using hydrogen as a co-combustion fuel with diesel oil on the temperature and hot gas emissions using a Computational Fluid Dynamics (CFD) simulation. The model was designed to match the characteristics and dimensions of a real experimental combustion setup, consisting of a combustion chamber, an inlet for diesel fuel, an air inlet for both combustion air and hydrogen, and an outlet stack for the hot gases. To validate the model prior to its application, a pure diesel combustion case was experimentally tested and compared with the simulation. The results confirmed that the model is sufficiently accurate for use, as the experimental and simulation results showed similar trends and behaviors. The flow rates of diesel and hydrogen were determined based on the calorific ratio that yielded the same total heat energy input to a combustion chamber. The studied ratios were 77:23 of diesel to hygrogen based on heating value. For each case, the combustion air flow rate was adjusted to achieve equivalence ratios (ϕ) of 0.65, 0.8, 0.95, and 1.1. The findings show that using hydrogen as a co-fuel results in a higher combustion temperature and a reduction in carbon dioxide (CO2) emissions compared to pure diesel combustion. Specifically, as the hydrogen ratio increases, the resulting temperature increases and the amount of CO2 decreases. Notably, combustion at an equivalence ratio (ϕ) of 1.1 resulted in the highest temperature and CO2 emissions among the tested equivalence ratios.